Biodegradable plastic mulch films increase yield and promote nitrogen use efficiency in organic horticulture - Samphire, Martin; Chadwick, David R.; Jones, Davey L. (Frontiers in Agronomy, 2023)
Plastic film mulches (PFM) are used extensively due to their ability to increase yield and suppress weed emergence. Their effects on plant-soil-microbial interactions, however, are less well understood. Organic systems rely on the supply of nutrients from organic sources (e.g., manures and fertility-building leys) and where poor N availability often limits yield. The issue is compounded by horticultural crops (e.g., lettuce) with a high N demand, but which are inefficient at recovering N from soil. The effect of PFM on the mineralisation of organic fertilisers and its interaction with other agronomic factors such as planting density is also less well-researched. We hypothesised that biodegradable PFM would be a useful tool to increase the efficiency of N management in organic horticulture by increasing the supply of available N leading to increased crop N uptake and crop yield, and simultaneously reducing N losses during the growing season. We conducted two field experiments under a temperate maritime climate with lettuces grown with either conventional (LDPE) PFM or a polylactic acid-based biodegradable PFM alongside un-mulched controls. The first experiment involved black or white coloured PFMs and two planting densities while the second experiment involved treatments with and without addition of poultry manure. Overall, yields were increased by 39% in both experiments with PFM, while soil mineral N concentrations were up to 5 times higher with PFM than without. Measurements of soil organic matter (SOM) turnover (Tea Bag Index) and soil CO2 efflux indicated a more rapid decay of SOM in the presence of the PFM. The use of PFM also promoted N use efficiency (NUE) by 300% in the presence of poultry manure. Denser planting with PFM resulted in proportionately higher yields. Higher yield and higher N concentrations (5-10%) in crop tissue in mulched plots resulted in higher total N uptake, however, total N uptake was low compared to soil concentrations: mulching with biodegradable PFM resulted in higher residual mineral N than un-mulched plots (77-147 mg kg-1 vs. 19 -70 mg kg-1). Our results are consistent with reduced N losses to the environment during the growing season and increased mineralisation under PFM. In conclusion, our findings support the adoption of PFM for organic horticulture and show that biodegradable PFM perform similarly to LDPE-based PFMs.